2000
DOI: 10.1002/1097-0061(20000630)17:2<95::aid-yea16>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Protein Interaction Screens Reveal Functional Networks Involving Sm-Like Proteins

Abstract: A set of seven structurally related Sm proteins forms the core of the snRNP particles containing the spliceosomal U1, U2, U4 and U5 snRNAs. A search of the genomic sequence ofSaccharomyces cerevisiaehas identified a number of open reading frames that potentially encode structurally similar proteins termed Lsm (L¯ Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
91
0
1

Year Published

2001
2001
2006
2006

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(104 citation statements)
references
References 55 publications
12
91
0
1
Order By: Relevance
“…Interestingly, the SSD1 gene, which affects lithium tolerance (see above) without significantly altering intracellular lithium accumulation (data not shown), also is able to associate with RNA (Uesono et al, 1997) and was identified as a general splicing mutant suppressor (Luukkonen and Seraphin, 1999). Finally, a novel yeast genomewide two-hybrid screen has revealed protein-protein interactions between the NST1/YNL091w gene product and Lsm4p, a Sm-like protein associated with spliceosome assembly (Fromont-Racine et al, 2000). Whether Nst1p directly determines the salt sensitivity of some RNA processing complex or Figure 6.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, the SSD1 gene, which affects lithium tolerance (see above) without significantly altering intracellular lithium accumulation (data not shown), also is able to associate with RNA (Uesono et al, 1997) and was identified as a general splicing mutant suppressor (Luukkonen and Seraphin, 1999). Finally, a novel yeast genomewide two-hybrid screen has revealed protein-protein interactions between the NST1/YNL091w gene product and Lsm4p, a Sm-like protein associated with spliceosome assembly (Fromont-Racine et al, 2000). Whether Nst1p directly determines the salt sensitivity of some RNA processing complex or Figure 6.…”
Section: Discussionmentioning
confidence: 98%
“…The preceding results indicate that the C-terminal motif of Prp24 is involved in substrate binding and contributes to U4/U6 formation in vivo+ As the C-terminal motif is not a known RNA-binding module, we investigated the possibility that it might mediate a protein-protein interaction with one or more of the Lsm proteins+ The ⌬10 mutation was therefore generated in appropriate two-hybrid constructs (Fromont-Racine et al+, 2000), and its interaction tested in combination with each of the U6-associated Lsm proteins (Lsm2-Lsm8) as well as Lsm1+ Because Lsm1, Lsm3, and Lsm4 did not interact with Prp24 in the two-hybrid screen (FromontRacine et al+, 2000), we included them here as direct tests of the interaction with Prp24, expecting that Lsm1 would not interact, as it is not found in the U6 snRNP (Stevens et al+, 2001)+ The interaction was monitored by activity of a b-galactosidase reporter and a histidine reporter, as shown for the Prp24-Lsm5 interaction using a b-galactosidase filter assay (Fig+ 5A) and growth on yeast plates lacking histidine (Fig+ 5B)+ The wild-type Prp24 showed a clear interaction with most of the Lsm proteins, as reported previously (Fromont-Racine et al+, 2000)+ In striking contrast, the ⌬10 mutation almost completely abolished this interaction (Fig+ 5A, B; Table 3), even though western analysis showed that Prp24⌬10 was expressed at essentially the same levels as wild-type protein (Fig+ 5C)+ The exceptions to the general trend are Lsm3, for which the interaction with wild-type Prp24 was no higher than the Lsm1 control despite a large effect of the ⌬10 mutation, and Lsm6, for which the ⌬10 mutation had almost no impact (Table 3)+ The disruption of two-hybrid interaction by the ⌬10 mutation was also observed when the truncated Prp24 fragment (amino acids 354-444) was used in this assay (data not shown), confirming that the last 90 amino acids of Prp24 are sufficient for Lsm interaction and demonstrating that the C-terminal motif is necessary+…”
Section: The C-terminal Motif Is Required For Prp24-lsm Interactionmentioning
confidence: 99%
“…Biochemical evidence for a role for the C-terminal motif in U4/U6 formation Our genetic data, along with extensive previous work on Prp24 (Shannon & Guthrie, 1991;Ghetti et al+, 1995;Jandrositz & Guthrie, 1995;Raghunathan & Guthrie, 1998;Vidaver et al+, 1999), suggested that the ⌬10 mutation might affect U4/U6 levels in vivo, and the biochemical experiments presented here demonstrate that this is indeed the case+ The ⌬10 mutation leads to a significant decrease (;3 times) in U4/U6 levels in vivo, consistent with Prp249s role in U4/U6 formation+ Furthermore, Prp24⌬10 coimmunoprecipitates only about half as much U6 as wild-type Prp24, even though U6 levels are approximately the same in the two extracts+ To elucidate the role of the C-terminal motif in U6 snRNP binding, we turned our attention to the Lsm proteins of the U6 snRNP+ Several lines of evidence suggest that a subset of the Lsm proteins interact with Prp24 and help to promote U4/U6 formation (Cooper et al+, 1995;Mayes et al+, 1999;Vidal et al+, 1999;Fromont-Racine et al+, 2000;)+ We used a two-hybrid assay to determine whether the C-terminal motif was important for this interaction+ The original screen found Prp24 as an interacting partner for Lsm2, 5, 6, 7, and 8+ We have now shown that Lsm4 also interacts with Prp24 by twohybrid; however, we failed to see an interaction with Lsm3+ In the absence of the C-terminal motif, the strength of the Prp24-Lsm interactions are reduced to the same level as the nonspecific control (Lsm1), except for the Prp24⌬10-Lsm6 interaction, which is still fivefold higher than the Prp24-Lsm1 interaction+ Taken together with the effect of the ⌬10 mutation on U4/U6 levels and on coimmunoprecipitation of U6, our data suggest that Prp24 binding to the Lsm proteins stabilizes its interaction with the U6 snRNP, and thereby promotes U4/U6 formation+ A cooperative model of Prp24-Lsm interaction does not exclude the possibility that either Prp24 or the Lsm2-Lsm8 complex can each promote U4/U6 formation without the other+ This has been demonstrated for Prp24, which accelerates base-pair formation between in vitrotranscribed U4 and U6 snRNAs 25-fold over the uncatalyzed rate (Ghetti et al+, 1995)+ It has also been demonstrated with the human Lsm proteins: Addition of biochemically purified human Lsm2-Lsm8 to in vitrotranscribed human U4 and U6 snRNAs stimulated the rate of base pairing approximately fivefold, apparently in the absence of any other proteins (Achsel et al+, 1999)+ The molecular consequences of proteins binding to U6 snRNA remain to be determined, but will certainly be important for understanding the mechanism of U4/U6 di-snRNP formation+ To demonstrate a direct role for the C-terminal motif in U4/U6 formation, we turned to an in vitro annealing assay described previously (Raghunathan & Guthrie, 1998)+ Our annealing data demonstrate a clear defect in U4/U6 formation with Prp24⌬10 at subsaturating protein concentrations+ The observation that wild-type and ⌬10 Prp24 have approximately the same maximum annealing rate under saturating conditions (high Prp24 concentration) indicates that the C-terminal motif ...…”
Section: A Conserved Lsm-interacting Motif In Prp24 1387mentioning
confidence: 99%
See 1 more Smart Citation
“…The LSM proteins provide an informative example of the integration of cellular protein machinery to couple synthesis and quality control in gene expression [2,11]. LSM proteins form heptameric complexes that bind to RNA molecules; one such complex is found primarily in the nucleus where it coordinates splicing of mRNAs, while a second, related, complex of LSM proteins assembles in the cytoplasm to monitor mRNA quality control.…”
Section: Incorporation Of Protein Domain Datamentioning
confidence: 99%